The Effect of Net Profit Margin and Total Asset Turnover on Return on Assets at PT Astra Otoparts Tbk for the 2014-2024 Period - Khoirunnisa; Hadijah Febriana (IJESS International Journal of Education and Social Science, 2026)
This study aims to determine the effect of Net Profit Margin and Total Asset Turnover on Return On Asset of PT Astra Otoparts Tbk in the period 2014 - 2024. This study uses secondary data obtained from the company's annual financial statements. The approach used is a quantitative method. Data analysis used is descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination tests, partial tests (t-test), and simultaneous tests (F-test), with the help of SPSS software version 25. The results of the study found that Net Profit Margin partially has a significant effect on Return On Asset, indicated by a significant value of 0.000 <0.05 and a calculated t value of 31.675> t table 2.306. While Total Asset Turnover shows partially has a significant effect on Return On Asset, with a significant value of 0.031 <0.05 and a calculated t value of 2.621> t table 2.306. Simultaneously, the Net Profit Margin and Total Asset Turnover variables have a significant effect on Return on Assets with a significance value of 0.000 < 0.05 and F count of 781.061 > 4.256.